Volitve v Ustavodajno skupščino leta 1920 na Slovenskem - Šela, Ana (Studia Historica Slovenica, 2022)
In the article, based on newspaper material and already published scientific literature, the two authors present the electoral struggle before the elections to the Constituent Assembly, which took place on November 28, 1920. In the introduction, they explain the political situation in Slovenian lands at that time, which was formed in a then new state, the Kingdom of Serbs, Croats, and Slovenians (Kingdom SHS). They particularly focus on the pre-election atmosphere in Slovenian lands and the election programs of the participating parties: the already established Slovenian People's Party, the Yugoslav Social Democratic Party and the Yugoslav Democratic Party, as well as the then new Independent Agricultural Party, the National Socialist Party, the Communist Party of Yugoslavia and the Prekmurje Economic Party.They conclude the article with an explanation about the course of the elections. They present the Act on Elections of National Deputies and the results of the elections in Slovenia, which were undoubtedly the result of the pre-election campaign in November 1920.
Keywords: 1920; catholic camp; Constituent Assembly; Constituent elections; delavski tabor; katoliški tabor; Kingdom of SHS; Kraljevina SHS; liberal camp; liberalni tabor; Slovenija; Ustavodajna skupščina; volilna kampanja; volitve